2022
DOI: 10.1038/s42003-022-03087-4
|View full text |Cite
|
Sign up to set email alerts
|

BrewerIX enables allelic expression analysis of imprinted and X-linked genes from bulk and single-cell transcriptomes

Abstract: Genomic imprinting and X chromosome inactivation (XCI) are two prototypical epigenetic mechanisms whereby a set of genes is expressed mono-allelically in order to fine-tune their expression levels. Defects in genomic imprinting have been observed in several neurodevelopmental disorders, in a wide range of tumours and in induced pluripotent stem cells (iPSCs). Single Nucleotide Variants (SNVs) are readily detectable by RNA-sequencing allowing the determination of whether imprinted or X-linked genes are aberrant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Among them, we found placental transcripts, such as FAM20A, PDE4D and ZC3H12C (Okae et al , 2014 ; Fig 1G ). Placental imprinted genes are highly expressed in the trophoblast cells of the placenta (Hanna, 2020 ; Martini et al , 2022 ), so we asked whether other markers of the TE lineage were induced after chemical resetting. We observed that 35 out of 107 expressed genes ( P ‐value = 4.27 × 10 −6 , Fisher's exact test) specifically expressed by TE cells in the human embryo (Xiang et al , 2020 ) were highly induced after chemical resetting (Fig 1H ), including KRT19, DAB2, LRP2 and TFAP2A (Fig 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, we found placental transcripts, such as FAM20A, PDE4D and ZC3H12C (Okae et al , 2014 ; Fig 1G ). Placental imprinted genes are highly expressed in the trophoblast cells of the placenta (Hanna, 2020 ; Martini et al , 2022 ), so we asked whether other markers of the TE lineage were induced after chemical resetting. We observed that 35 out of 107 expressed genes ( P ‐value = 4.27 × 10 −6 , Fisher's exact test) specifically expressed by TE cells in the human embryo (Xiang et al , 2020 ) were highly induced after chemical resetting (Fig 1H ), including KRT19, DAB2, LRP2 and TFAP2A (Fig 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of imprinted gene expression on a bulk tissue level raises the question of whether the observed allelic bias is reflected in every cell of the lysate in the same way, or whether individual cells differ in their mono-/bi-allelic transcriptional status of the gene and, thus, deviate from the tissue average. Large-scale single-cell imprinted gene expression analysis is still in its infancy, but novel approaches indicate that not all cells of a tissue might show the same allelic expression status ( Martini et al, 2022 ). To address this question specifically for the Peg13 imprinting cluster, we isolated single NSCs from C57BL/6J × Cast/EiJ neurospheres as well as single neurons differentiated from these in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Due to advances in technology, especially single-cell transcriptomics and highly sensitive in situ hybridization methods, it has now become possible to investigate imprinted gene expression on the cellular level ( Varrault et al, 2020 ; Martini et al, 2022 ). Instead of a single-cell RNA-seq approach, we used the sc-GEM method ( Lorthongpanich et al, 2013 ; Cheow et al, 2015 ; Cheow et al, 2016 ) for a more limited analysis of the genes of this imprinting cluster in single cultured NSCs and differentiated neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of existing RNA-seq datasets can be used to identify ASE of imprinted genes beyond evaluation of gene expression, thereby detecting the LOI of imprinted genes ( 150 ). However, when heterogeneous populations of cells, such as cancer samples, are analyzed, only single-cell measurements allowed the detection of widespread LOI events ( 151 ). Therefore, the use of effective and appropriate data analysis methods to analyze single-cell transcriptomic data will provide a major advantage in the analysis of tumor epigenetic aberrations.…”
Section: Detecting Methods Of Loi Genes In Cancersmentioning
confidence: 99%
“…Therefore, the use of effective and appropriate data analysis methods to analyze single-cell transcriptomic data will provide a major advantage in the analysis of tumor epigenetic aberrations. For example, BrewerIX, a standardized approach for the analysis of known imprinted genes, can be used to analyze RNA-seq data from single breast cancer cells to identify LOI of imprinted genes ( 151 ). Differential allelic expression using single-cell data (DAESC), a powerful method for differential ASE analysis using single-cell RNA sequencing (scRNA-seq) from multiple individuals, is capable of analyzing genes with differential ASE in pancreatic endocrine cells from patients with type 2 diabetes and controls, taking into account the effect of allelic switching, although it is not suitable for estimating cancer cells ( 152 ).…”
Section: Detecting Methods Of Loi Genes In Cancersmentioning
confidence: 99%